Blood Donation and Transfusion Medicine in the Spanish Press - Bomfim de Souza, Mariluce Karla; Santoro Domingo, Pablo (Revista Española de Comunicación en Salud, 2020)
Introduction: The media play a fundamental role when it comes to promoting blood donation and building the symbolic values and contents associated with it. Objective: The aim of this study was to analyze the ways in which press treats blood donation and other issues related to transfusion medicine, based on an analysis of news published in the main newspapers of Spain during the year 2016. Methods: From a search conducted in the newspapers El Pais, El Mundo, ABC, La Vanguardia, El Confidencial and eldiario.es, 332 news items were selected. A simple frequency statistical analysis was performed, as well as a content analysis. Results: News items were classified by topic, finding that 45.5% of the news referred campaigns and calls for donation; 26.8% addressed organizational issues related to transfusion services and resources;19.6% dealt with medical research and therapeutic innovations; and 11.4% addressed didactic or educational issues. In addition, 24.4% of the news explicitly mentioned values such as altruism, generosity or solidarity, while 29.8% referred to specific territories or made comparisons between autonomous communities. Conclusions: We identified five functions that newspapers fulfill regarding the promotion and symbolic construction of blood donation: appealing, didactic, futuristic, ideological and construction of collective identities.